Post Traumatic Tuberculous Tenosynovitis in a Patient that Manifests as Soft Tissue Tumor: A Case Report - Haryo N. Yahya; Hadi, Usman (Institute of Medico-legal Publications Pvt Ltd, 2022)
Mycobacterium tuberculosis infection is one of the oldest diseases of the human race. This bacteriacan attack any organ in the human body. Extra Pulmonary Tuberculosis (EPTB) infection diagnosis arerarely straightforward, and in many cases, delayed due to various reasons. Tuberculous tenosynovitis(inflammation of the tendon and its capsule because of Mycobacterium tuberculosis complex infection)is a rare form of EPTB. Tuberculosis infection at sites of previous trauma have been reported consistentlythough rarely. We present the case of a 48 years old male with complains of lumps on his lower left arm(with prior history of blunt trauma on the location) and progressive inability to flex the fingers of his lefthand. Early examinations suggest the diagnosis to be a soft tissue tumour. However, tissue biopsy latershowed that the patient was actually suffering from tuberculosis infection. The patient later showedsatisfying response to tuberculosis medication on subsequent follow ups.